International Approaches to Rape - Westmarland, Nicole; Gangoli, Geetanjali (Policy Press, 2011)
By introducing readers to national perspectives of issues relating to rape, the book presents a comparative approach which highlights similarities and differences between countries, contexts, laws, key issues and policies and interventions.
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Social Science / Criminology; Social sciences; Electronic books